Exploring the Role of GLP-1 Receptor Agonists in Alzheimer’s Disease: A Review of Preclinical and Clinical Evidence - Lívia C. R. Teixeira; Marcelo R. Luizon; Karina B. Gomes (Receptors)
Glucagon-like peptide-1 receptor agonists (GLP-1RAs), including dulaglutide, liraglutide, semaglutide, and exenatide, are effective treatments for type 2 diabetes mellitus (T2DM) and obesity. These agents mimic the action of the endogenous incretin glucagon-like peptide-1 (GLP-1) by enhancing insulin secretion, inhibiting glucagon release, and promoting weight loss through appetite suppression. GLP-1RAs have recently been suggested to have neuroprotective effects, suggesting their potential as treatment for neurodegenerative disorders, such as Alzheimer’s disease (AD). AD and T2DM share several common pathophysiological mechanisms, including insulin resistance, chronic inflammation, oxidative stress, and mitochondrial dysfunction. These shared mechanisms suggest that therapeutic agents targeting metabolic dysfunction may also be beneficial for neurodegenerative conditions. Preclinical studies on GLP-1RAs in AD models, both in vitro and in vivo, have demonstrated promising neuroprotective effects, including reductions in amyloid-beta accumulation, decreased tau hyperphosphorylation, improved synaptic plasticity, and enhanced neuronal survival. Despite the encouraging results from preclinical models, several challenges need to be addressed before GLP-1RAs can be widely used for AD treatment. Ongoing clinical trials are investigating the potential cognitive benefits of GLP-1RAs in AD patients, aiming to establish their role as a therapeutic option for AD. This review aimed to examine the current literature on preclinical and clinical studies investigating GLP-1 receptor agonists as potential therapeutic agents for AD.